Activation of p38 Mitogen-Activated Protein Kinase Is Inhibited by Hyaluronan via Intercellular Adhesion Molecule-1 in Articular Chondrocytes Stimulated With Type II Collagen Peptide - Tadashi Yasuda (Journal of Pharmacological Sciences, 2012)
This study examined the activation of p38 mitogen-activated protein kinase with matrix metalloproteinase-13 (MMP-13) production by a synthetic peptide derived from type II collagen (CB12-II) and its inhibition by high molecular weight hyaluronan (HA) in chondrocytes. When cartilage explants or isolated chondrocytes in monolayer were incubated with CB12-II, the peptide (50 μM, 72 h) activated p38 in association with enhanced MMP-13 production. Inhibition studies with SB203580 (0.1 – 1 μM) indicated the requirement of p38 for CB12-II–induced MMP-13 production. Pretreatment with 2700 kDa HA (1 mg/ml, 1 h) resulted in significant suppression of CB12-II–stimulated MMP-13 production in cartilage as well as in chondrocyte monolayer cultures. HA (1 mg/ml) suppressed p38 activation by CB12-II, leading to a decrease in MMP-13 production. The antibody (20 μg/ml) to intercellular adhesion molecule-1 (ICAM-1), which has been recognized as a receptor of HA on chondrocytes, reversed the HA effect on CB12-II action. Thus, the present study clearly demonstrated that high molecular weight HA suppressed CB12-II–activated p38 via ICAM-1 in articular chondrocytes. HA could down-regulate the catabolic action of type II collagen fragments in osteoarthritic joints through the mechanism demonstrated in this study. Keywords:: osteoarthritis, type II collagen fragment, hyaluronan, intercellular adhesion molecule-1 (ICAM-1), p38